Implementation Science and Implementation Science Communications: our aims, scope, and reporting expectations - Sales, Anne; Wilson, Paul M.; Wensing, Michel; Aarons, Gregory A.; Armstrong, Rebecca; Flottorp, Signe; Hutchinson, Alison M.; Presseau, Justin; Rogers, Anne; Sevdalis, Nick; Squires, Janet; Straus, Sharon; et al. (Implementation science, 2019)
In the 13 years since the inception of Implementation Science, we have witnessed a continued rise in the number of submissions, reflecting the growing global interest in methods to enhance the uptake of research findings into healthcare practice and policy. We now receive over 800 submissions annually, and there is a large gap between what is submitted and what gets published. To better serve the needs of the research community, we announce our plans to introduce a new journal, Implementation Science Communications, which we believe will support publication of types of research reports currently not often published in Implementation Science. In this editorial, we state both journals’ scope and current boundaries and set out our expectations for the scientific reporting, quality, and transparency of the manuscripts we receive.
Gesehen am 10.06.2020